2020
DOI: 10.1017/dmp.2019.140
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Effectiveness of Interventions Provided to First Responders to Prevent and/or Treat Mental Health Effects of Response to a Disaster: A Systematic Review

Abstract: Objectives: This review systematically explores the current available evidence on the effectiveness of interventions provided to first responders to prevent and/or treat the mental health effects of responding to a disaster. Methods: A systematic review of Medline, Scopus, PsycINFO, and gray literature was conducted. Studies describing the effectiveness of interventions provided to first responders to prevent and/or treat the mental health effects of responding to a disaster were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The GEMLR platform has been used to evaluate narrower topics in systematic reviews published elsewhere. [19][20][21][22] Recognizing that important clinical guidance is at times also found in non-peer-reviewed "gray" literature produced by various international organizations, 23 we also supplement the review of published literature with a manual search and review of new guidance found on the websites of several key organizations, including academic think thanks and prominent humanitarian governmental and nongovernmental organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The GEMLR platform has been used to evaluate narrower topics in systematic reviews published elsewhere. [19][20][21][22] Recognizing that important clinical guidance is at times also found in non-peer-reviewed "gray" literature produced by various international organizations, 23 we also supplement the review of published literature with a manual search and review of new guidance found on the websites of several key organizations, including academic think thanks and prominent humanitarian governmental and nongovernmental organizations.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, five systematic reviews have attempted to synthesize the effectiveness of interventions for reducing psychological distress among first responders, especially PTSD [2,[18][19][20][21]. Smith and Robert [18] identified a range of studies that tested interventions to reduce stress and PTSD among emergency ambulance personnel, and they found that all included articles (10 studies) had a lack of quality due to their methodological flaws such as, self-selection of groups and inadequate timing of the interventions.…”
Section: Introductionmentioning
confidence: 99%
“…They found that trauma focused therapies can be effective for first responders, but faced some limitations such as, the small sample sizes of most included studies and few investigations with any control condition. Winders et al [20] examined the prevention and treatment of psychiatric symptoms in first responders and how effectiveness was related to the income level of the country. They found, in 25 eligible studies, that most interventions were effective for preventing and treating psychological illness in first responders in all three levels of income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing that global morbidity and mortality is in many ways shifting away from acute infectious conditions to chronic diseases and emergency conditions, 16 we aim to provide a platform that recognizes publications that directly improve patient care in the acute setting, especially in areas with limited medical resources. Given the diversity of topics covered, we do not attempt a formal systematic review or meta‐analysis in this current review but do evaluate specific topics in separate systematic reviews 17–19 …”
mentioning
confidence: 99%
“…Given the diversity of topics covered, we do not attempt a formal systematic review or meta-analysis in this current review but do evaluate specific topics in separate systematic reviews. [17][18][19] In addition to the published peer-reviewed literature, GEMLR also includes an extensive manual search of the gray literature produced by a variety of think tanks, academic organizations, and nongovernmental organizations. Written to be more immediately applicable to clinicians and policy-makers in the field, gray literature has the potential to make an important contribution to systematic reviews such as GEMLR.…”
mentioning
confidence: 99%